Nanotechnology for dummies. - Booker, Richard (Wiley Publishing, 2005)
"Have you been reading the latest science magazines and noticed that the word "nano" has become as ubiquitous as the word "calorie" in a diet book? Are you looking for the latest hot investment opportunity and you've hear that something called nanotechnology will someday revolutionize our lives, and quite possibly your portfolio? Well, you've come to the right place! nanotechnology for dummies is a fantastic way to get beyond all the hype and really understand what nanotechnology is and where it's headed. This is no dry, scientific journal; what you hold in your hands is a book that gives you just what you need to comprehend the basic concepts of nanotechnology, discover what nanotechnologists are making happen today, and get a look at he groundwork for tomorrow's nano-applications." (Copiado de la introducción).